Dynamics of Calcium Signal and Leukotriene C4 Release in Mast Cells Network Induced by Mechanical Stimuli and Modulated by Interstitial Fluid Flow (Advances in Applied Mathematics and Mechanics, 2018)
Mast cells (MCs) play an important role in the immune system. Throughconnective tissues, mechanical stimuli activate intracellular calcium signaling pathways,induce a variety of mediators including leukotriene C$_4$(LTC$_4$) release, and affectMCs' microenvironment. This paper focuses on MCs' intracellular calcium dynamicsand LTC$_4$ release responding to mechanical stimuli, explores signaling pathways inMCs and the effect of interstitial fluid flow on the transport of biological messengersand feedback in the MCs network. We use a mathematical model to show that (i)mechanical stimuli including shear stress induced by interstitial fluid flow can activatemechano-sensitive (MS) ion channels on MCs' membrane and allow Ca$^{2+}$ entry,which increases intracellular Ca$^{2+}$ concentration and leads to LTC$_4$ release; (ii) LTC$_4$ in the extracellular space (ECS) acts on surface cysteinyl leukotriene receptors (LTC$_4$R)on adjacent cells, leading to Ca$^{2+}$ influx through Ca$_{2+}$ release-activated Ca$^{2+}$ (CRAC)channels. An elevated intracellular Ca$^{2+}$ concentration further stimulates LTC$_4$ releaseand creates a positive feedback in the MCs network. The findings of this studymay facilitate our understanding of the mechanotransduction process in MCsinduced by mechanical stimuli, contribute to understanding of interstitial flow-relatedmechanobiology in MCs network, and provide a methodology for quantitatively analyzingphysical treatment methods including acupuncture and massage in traditionalChinese medicine (TCM).